PENGARUH KINERJA KEUANGAN, KEBIJAKAN HUTANG DAN PERTUMBUHAN POTENSIAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN BUMN DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Tri Nurindahyanti Yulian; Fuji Windya Sari; Aziz Zahari (JURNAL EKONOMI, 2019)
This Study aims at analizyng the ratio ROA, DAR and Growth through Dividend Policy in State Owned Enterprises (BUMN). In this case the researcher used financial statements data of the State Owned Enterprises (BUMN) registered Indonesian Stock Exchange and has been published. The researcher uses 12 from 20 State Owned Enterprises (BUMN) listed in Indonesian Stock Exchange in 2015-2017 by using purposive random sampling. Based on the analysis of the data, it can be concluded that the variables ROA influence through dividend policy, the variables DAR does not influence in dividend policy and the variables Growth does not influence in dividend policy. For investors who wants to invest should pay attention on financial performance level. For the company entity should pay attention on debt policy, because that’s variables has a high effect for sustainability of the company. For the next researcher should be able to measure by replacing or adding other variables for the maximize results. Keywords: ROA, DAR, Growth and Dividend Policy